CULTURAL MAPPING OF THE ISLAND PROVINCE OF MARINDUQUE, PHILIPPINES: BASIS FOR ARTS CONSERVANCY AND HUMANITIES INDIGENIZATION IN EDUCATION - Asuncion, Rex Emmanuel (International Journal of Arts, Sciences and Education, 2022)
The study aimed to produce a list of local artworks and to identify the channels of humanities like music, dance, theater, sculpture, architecture, painting, gustatory arts in cuisines, and fine art present in the people, local culture, and living traditions. Alongside the aforesaid purpose is to promote and invigorate potential scenic spots for tourism and leisure found in the island Province of Marinduque, Philippines. This paper explored the unseen and current arts manifested in the lifestyle of Marinduqueños/Marindukanons. The unheard and undocumented folksongs and dances of the low-land Christians were influenced by the Spaniards, the language in the art of communication, woodcarvings and handicrafts empowered by local culture and the booming business industry, the food uniquely cooked on the island, the expressions of architecture, the religious theater presentations as public entertainment, the traditions which are greatly influenced by the Catholics are evident in the lifestyle of the Marindukanons. The island’s panoramic setting is surrounded by great bodies of water, islets, white sands, waterfalls, rivers, caves, a dormant volcano, hot springs, and other rock formations that are abundant natural treasures. The results of the paper presented the religious artifacts, political policies, arts, and cultural transformations that served as identifying elements of the province. Through the years, the turn of events has transformed the Marindukanons and their localities into a potential tourist haven in the future. These abundant man-made natural beauties and treasures are all waiting to be discovered, experienced, and shared to the whole world.